African Economic Integration Development in Technological Transformation: Accessing the Importance of Ethical Leadership for Policy Implementation in SADC - Enaifoghe, Andrew; Dlamini, Nomaswazi P.; Agwuna, Leonard U. (Journal of Economics and Behavioral Studies, 2021)
Most African states have suffered from severe macroeconomic disequilibria, foreign debt service burdens, and over-valued currencies. The lack of ethical leadership on policy implementation has led most Africa countries to linger highly behind in terms of development. Many countries are reliant on agriculture and yet suffer from high levels of unemployment and food insecurity on the continent. In these situations, it is logical for one to expect the full integration of Africa in terms of trade and migration, using the Southern African sub-regional integration as a case study. This study looks at the Southern African economic integration development and the importance of having ethical leadership for policy implementation. Qualitatively, this paper collected data and analysis them based on content, using secondary sources from different domains. The neo-Functionalist theory was applied and findings show that there is a failure to meet set targets in the SADC plan which has established a bad precedent for the sub-regions for African development, the failure is seen as lacking ethical leadership. It recommends that there is a need for African states to improve its infrastructure, recognise the capacity of the private sector to generate wealth and induce development, with open economies to member’s states.